Cerebrospinal fluid adenosine deaminase levels as a diagnostic marker in tuberculous meningitis in adult Nepalese patients - Chander, Anil (Asian Pacific Tropical Medicine Press, 2013)
OBJECTIVE: To study the cerebrospinal fluid (CSF) adenosine deaminase (ADA) levels in tuberculous meningitis (TBM) and non-TBM -viral meningitis cases and to determine its diagnostic significance as a biochemical marker of TBM infection. METHODS: The study population comprised two different patient groups. TBM - group I - 28 cases and non-TBM-viral meningitis - 22 cases. These were enrolled consecutively in the study and CSF specimens were collected from them. ADA estimation was carried out by spectrophotometry. RESULTS: ADA levels (mean±SD) in the TBM and non-TBM groups were 16.46±6.24 U/L and 5.13±2.96 U/L, respectively (highly significant P<0.001). Using a CSF ADA cut off reference value of >10 IU/L, the test showed a good sensitivity of 82.14% (95% CI 64.41-92.12) and a high specificity of 90.91% (95% CI 72.19-97.47). Positive and negative predictive value and positive and negative likelihood ratios and accuracy of the test in TBM cases were 92% (95% CI 75.03-97.77), 80% (95% CI 60.86-91.13), 9.03 (95% CI 2.38-34.25), 0.19 (95% CI 0.09-0.44) and 86%, respectively. CONCLUSION: CSF ADA levels are elevated in the TBM cases as compared to the non-TBM - viral meningitis cases with a good sensitivity and a high specificity. It is a simple and inexpensive diagnostic adjunctive test in the rapid and early diagnosis of TBM.